1998
DOI: 10.3109/03005364000000069
|View full text |Cite
|
Sign up to set email alerts
|

Attitude to Hearing Diffculty and Hearing Aids and the Outcome of Audiological Rehabilitation

Abstract: First time hearing aid candidates (N = 135) in a NHS setting were administered the Hearing Attitudes in Rehabilitation Questionnaire (HARQ) designed to assess attitudes to acquired hearing loss and hearing aids and 92% of them were followed up 3-9 months after fitting. Attitude scores, age, sex and sensory thresholds were related to six self-report outcome measures by use of logistic regression. The major findings were that patients who were least distressed by their hearing difficulties and reported not wanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
67
0
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 14 publications
4
67
0
6
Order By: Relevance
“…Studies that have investigated gender effects have mostly found none (Hickson et al, 1999;Jerram and Purdy, 2001). Female participants were slightly more satisfied than male participants in the study by Brooks and Hallam (1998).Besides age and gender, other demographic characteristics, such as whether living alone or with others and socioeconomic status, have not been found to be related to satisfaction (Gatehouse, 1994;Norman et al, 1994;Hickson et al, 1999;Jerram and Purdy, 2001).In summary, age, gender and other demographic data exhibit no impact or minimal effect on satisfaction. …”
mentioning
confidence: 83%
See 3 more Smart Citations
“…Studies that have investigated gender effects have mostly found none (Hickson et al, 1999;Jerram and Purdy, 2001). Female participants were slightly more satisfied than male participants in the study by Brooks and Hallam (1998).Besides age and gender, other demographic characteristics, such as whether living alone or with others and socioeconomic status, have not been found to be related to satisfaction (Gatehouse, 1994;Norman et al, 1994;Hickson et al, 1999;Jerram and Purdy, 2001).In summary, age, gender and other demographic data exhibit no impact or minimal effect on satisfaction. …”
mentioning
confidence: 83%
“…• Participants have various degrees of loss but direct comparison cannot be made across studies as some studies have reported average hearing level only (ie, Gatehouse, 1994;Brooks and Hallam, 1998), and some reported hearing in the better ear (eg, Brooks and Hallam, 1998;Purdy and Jerram, 1998 Scales set a priori, not evaluated for validity …”
Section: Methodologies Of Hearing Aid Satisfaction Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a growing awareness in audiological practice that attention to technical matters alone may miss the point as far as the individual's needs and social circumstances are concerned (Noble 1996, Brooks 1990, Falkenberg & Antonsen 1997, Brooks & Hallam 1998, Antonsen 2001. For instance, the fact is neglected that the educational audiologist is a necessary part of the audiological team (Lippestad 1994, Tesch-Rö mer 1996, Hétu 1996, Lippestad & Natvig Aas 1997, Gundersen & Lippestad 2000, Norwegian Board of Health 2000, Antonsen 2001).…”
Section: Current Situation In Aural Rehabilitationmentioning
confidence: 99%